Intestinal dysbiosis – a new treatment target in the prevention of colorectal cancer - Florinela-Andrada Dumitru; Sergiu Ioan Micu; Roxana Emanuela Popoiag; Marilena Musat; Andreea Daniela Caloian; Valentin Calu; Vlad Denis Constantin; Daniela Gabriela Balan; Cornelia Nitipir; Florin Enache (Journal of Mind and Medical Sciences)
The gastrointestinal microbiome contains at least 100 trillion microorganisms (bacteria, viruses, fungi), whose distribution varies from the mouth to the rectum spatially and temporally throughout one's lifetime. The microbiome benefits from advancing research due to its major role in human health. Studies indicate that its functions are immunity, metabolic processes and mucosal barrier. The disturbances of these functions, dysbiosis, influence physiology, lead to diabetes, inflammatory bowel disease, obesity and colon tumorigenesis. The third most common form of cancer, colorectal cancer, is the result of many factors and genes, and although the link between dysbiosis and this type of cancer is poorly characterized, it has been shown that some bacterial species and their metabolites have a critical role in developing colorectal cancer. Also, gut microbiota plays a role in the inflammatory response and immune process perturbations during the progression of colorectal cancer. Some new technologies, such as metagenome sequencing, facilitated the progress by analyzing the metabolic and genetic profile of microbiota, revealing details about the bacterial composition, host interactions, and taxonomic alterations. This review summarizes the studies regarding the link between gut microbiota and colorectal cancer, targeting new therapeutic strategies.